Partial discharge measurement of void in insulation system using HDPE - Qaid Algobi, Mohammed Hamood (2021)
Partial discharge plays important role in decision system of high voltage industry. In measurement of partial discharge test, the exact detection for the void and insulation machine fault in advance is needed in the high voltage equipment to ensure the early maintenance for long durability, to avoid the collapse in the machine and to evade the high cost for machine downtime maintenance. There are many ways to detect the existence of partial discharge such as wire and wireless sensors which are the most popular used. There are many types of wire sensors have been developed such as the high frequency current transformer (HFCT) sensor that detect existence of partial discharge by connected with high voltage (HV) apparatus or equipment. In our partial discharge test experiments, three plates surface of High-Density Poly Ethelene (HDPE) have been used that consist of two plain plates and the third plate with void and the void has three sizes which are (8 mm, 10 mm, and 12 mm). The void location for each size change to different position that include the first position (top), second position (middle), and the third position (bottom) for each plate with its certain size. The partial discharge test in our experiments used the HFCT sensor in order to measure the PD existence at insulation system. In the first phase of our partial discharge test experiments the HFCT sensor detect the PD signal and the signal waveform that performed at oscilloscope as input data for the next phase. While, in the second phase the data analyzed by using MATLAB Software in order to extract the most effected charge values on the insulation system in which the signal waveform analyzed to find the PD charge by calculate the area under the waveform. Finally, the last phase shows the output results of the experiments for all size of voids with its selected values 8 mm, 10 mm, and 12 mm. From the analysis, found that the PD appear at lower voltages when the void is positioned at the top of the layer (position 1) compared to other positions. Our second finding is that if the size of the void is larger, the PD appear at lower voltages.